2015
DOI: 10.1891/0886-6708.vv-d-13-00011
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Victims Informed: Service Providers’ and Victims’ Experiences Using Automated Notification Systems

Abstract: Automated victim notification is often touted as an effective and efficient means for providing victims timely and accurate information of their offenders' court events and status changes at reduced burden to the criminal justice system. Today, 47 states, the District of Columbia, and Puerto Rico have some form of automated notification system. Researchers surveyed 1,246 service providers and 723 victims to examine their awareness and use of, satisfaction with, and experiences using automated notification syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In response to problems around crime victims' receipt of information about court hearings and outcomes, automated methods for communicating with victims have been developed in the US. These systems have been rolled out over nearly 30 years and were operating in 47 states by 2015 (Irazola et al 2015). These systems provide victims with the opportunity to sign up to receive notifications about scheduled court hearings and outcomes via a range of mechanisms, including telephone, email and text message (United States Department of Justice 2020).…”
Section: Automated Victim Notification Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to problems around crime victims' receipt of information about court hearings and outcomes, automated methods for communicating with victims have been developed in the US. These systems have been rolled out over nearly 30 years and were operating in 47 states by 2015 (Irazola et al 2015). These systems provide victims with the opportunity to sign up to receive notifications about scheduled court hearings and outcomes via a range of mechanisms, including telephone, email and text message (United States Department of Justice 2020).…”
Section: Automated Victim Notification Systemsmentioning
confidence: 99%
“…While there is little literature on the operation and effectiveness of such systems, Irazola et al (2015) found that victims who subscribed to these systems indicated that the notifications helped them to feel more empowered and safe and made them want to be more involved in their case (for discussion, see also Healy 2019). Accordingly, we recommend that similar systems be considered in the Australian context.…”
Section: Automated Victim Notification Systemsmentioning
confidence: 99%
“…Increasingly standard in larger jurisdictions, automated systems use the victim’s preferred communication format (i.e., email, telephone, or mail) and the victim’s registration to a system to improve privacy. Some of these notification systems are open to the public while others are specialized for victims and criminal justice professionals (Irazola, Williamson, Niedzwiecki, Debus-Sherril, & Stricker, 2013). An evaluation of one Statewide Automated Victim Information and Notification (SAVIN) found benefits to closed systems including victim-specific information.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Benefits were also found to open systems including increased access to knowledge for a wider group. SAVIN is most effective when victims control their contact option, are required to register only once, and can use effectively developed instructions (Irazola et al, 2013). A North Carolina SAVIN evaluation drew on the input of 47 criminal justice professionals and 41 crime victims of all types, including IPV.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In hundreds of thousands of cases, completed rape kits have been left to founder in police storage facilities throughout the country (Campbell, Fehler-Cabral et al, 2017; Campbell et al, 2015; Strom et al, 2009). While a growing body of literature provides guidance for tackling the backlog of untested rape kits (Busch-Armendariz & Sulley, 2015; Busch-Armendariz, Donde et al, 2015; Campbell, Fehler-Cabral et al, 2017; Campbell & Fehler-Cabral, 2018; Irazola et al, 2015), few studies have examined the rape kit backlog through the eyes of survivors. This study seeks to fill this gap in the literature by conducting a phenomenological interpretive analysis of survivors’ experiences with unsubmitted rape kits to better understand their initial expectations, how it felt when those expectations were not met, and how they responded to the systemic failure to test their kits.…”
mentioning
confidence: 99%